2019
DOI: 10.2147/opth.s224454
|View full text |Cite
|
Sign up to set email alerts
|

<p>Disaster Preparedness Impact In A Complex Ophthalmology Practice: A Review Of Patients Receiving Intravitreal Injections</p>

Abstract: Purpose: A private tertiary care ophthalmology practice was analyzed to see how Hurricane Irma affected patient care. Methods: Eighty-two patients (96 eyes) that missed their scheduled appointments due to Hurricane Irma were reviewed. Patients were being treated with intravitreal injection therapy for diabetic retinopathy, radiation retinopathy, vein occlusions, choroidal neovascularization, or neovascular age-related macular degeneration. The authors assessed patients' visual acuity and macular thickness chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Teleophthalmology, mainly via portable devices, has the capacity to bridge accessibility gaps in remote and underserved communities. Research has demonstrated the feasibility of cost-effective DR screening tools utilizing smartphones and telemedicine, resulting in improved DR screening coverage in rural areas [ 15 ]. Furthermore, advancements in laser photocoagulation devices have enhanced precision and user-friendliness, making them well-suited for integration into telemedicine, thus enabling remote real-time consultation and expert care, which in turn improves therapeutic outcomes and reduces collateral retinal damage in the context of DR treatment [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Teleophthalmology, mainly via portable devices, has the capacity to bridge accessibility gaps in remote and underserved communities. Research has demonstrated the feasibility of cost-effective DR screening tools utilizing smartphones and telemedicine, resulting in improved DR screening coverage in rural areas [ 15 ]. Furthermore, advancements in laser photocoagulation devices have enhanced precision and user-friendliness, making them well-suited for integration into telemedicine, thus enabling remote real-time consultation and expert care, which in turn improves therapeutic outcomes and reduces collateral retinal damage in the context of DR treatment [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Remarkably, as highlighted in Table 2, a significant portion of the reviewed studies evaluated the implications of delays in administering anti-vascular endothelial growth factor (anti-VEGF) treatment to patients with DR during the COVID-19 pandemic [14][15][16][17][18][19][20][21]. Noteworthy advances in DR screening and diagnostic technologies were a recurrent theme across multiple studies [22][23][24][25][26][27][28].…”
Section: Table 1: Distribution Of Study Types In the Reviewed Literaturementioning
confidence: 99%
See 1 more Smart Citation